Arhiva Medievală a Romăniei - Universitatea din Bucureşti (2014)
The Medieval archive of Romania is a database created within the project “Digitization of the medieval documents from the National Archives of Romania”. The project was implemented by The University of Bucharest, in partnership with The National Archives of Romania, Babeș-Bolyai University in Cluj-Napoca and The National Archives of Norway. The database comprises the documents issued up to 1600, regardless of the preservation form, which are in the repositories of the National Archives and in other archives of Romania.